Microworlds and Programming, Microworlds as Vehicles for Learning: Introducing Microworlds as Means of Providing Scaffolding for Learners With Specific Needs and for Teachers to Increase Their Computational Fluency (Constructionism Conference Proceedings, 2025)
Come learn how to create microworlds which customize programming environments as a form of scaffolding for learners of specific needs, ages, or ability levels. Along the way, you will bring powerful ideas from Bruner, Perkins, and the Reggio Emilia approach to life in your teaching while developing your own computing fluency.